2005
DOI: 10.1158/0008-5472.can-05-1302
|View full text |Cite
|
Sign up to set email alerts
|

Genistein, a Dietary Isoflavone, Down-Regulates the MDM2 Oncogene at Both Transcriptional and Posttranslational Levels

Abstract: Although genistein has chemopreventive effects in several human malignancies, including cancers of the breast, colon, and prostate, the mechanisms of action are not fully understood. Herein we report novel mechanisms whereby genistein down-regulates the MDM2 oncogene, perhaps explaining some of its anticancer activities. In a dose-and time-dependent manner, genistein reduced MDM2 protein and mRNA levels in human cell lines of breast, colon, and prostate cancer; primary fibroblasts; and breast epithelial cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
104
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(108 citation statements)
references
References 40 publications
(63 reference statements)
4
104
0
Order By: Relevance
“…In addition, the ectopic activation of NFAT1 activates c-Myc, which is a critical mechanism for pancreatic cancer cell growth in vitro and in vivo (29,30). In our previous work, we have demonstrated that the mdm2 transcription is down-regulated by a dietary isoflavone, genistein, in multiple cancer cell lines (31). Although the underlying mechanism is not fully understood, our preliminary results suggest that the NFAT transcription factors may be involved in the regulation of mdm2 mRNA expression.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…In addition, the ectopic activation of NFAT1 activates c-Myc, which is a critical mechanism for pancreatic cancer cell growth in vitro and in vivo (29,30). In our previous work, we have demonstrated that the mdm2 transcription is down-regulated by a dietary isoflavone, genistein, in multiple cancer cell lines (31). Although the underlying mechanism is not fully understood, our preliminary results suggest that the NFAT transcription factors may be involved in the regulation of mdm2 mRNA expression.…”
mentioning
confidence: 73%
“…Colony Formation, Apoptosis, Quantitative PCR, and Luciferase Reporter Assays-The colony formation assay, cell apoptosis assay, quantitative PCR assay, and luciferase reporter assay were performed as described previously (31).…”
Section: Methodsmentioning
confidence: 99%
“…These nutrients have protective effects against colorectal cancer. Previous studies have shown that these nutrients can maintain DNA synthesis and methylation (Mason et al, 1996), modulate signal pathways in malignant transformation (Li et al, 2005), inhibit cell growth and induce apoptosis (Bennink, 2001). Foods that lack these nutrients are related to an increased risk of colorectal cancer (Potter, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…2). A few of flavonoids were found to inhibit expression of mdm2 (21,37). Mdm2 can be phosphorylated by AKT (28,38), which increases stability of mdm2.…”
Section: Discussionmentioning
confidence: 99%